ANALISIS BREAK EVEN POINT USAHA PEMBIBITAN KARET (Hevea brasiliensis L) OKULASI DI DESA BENTOK DARAT KECAMATAN BATI-BATI KABUPATEN TANAH LAUT PROVINSI KALIMANTAN SELATAN - Yan Yozef Agus Suratman (Chlorophyl, 2021)
This research aims are: (1). Knowing the technical description of grafting rubber seedlings carried out by farmers; (2) knowing how much the costs, revenues, and profits of the grafting rubber nursery business are; (3) determine the break even point of grafting rubber nursery business in Bentok Darat Village, Bati-Bati Sub-district. This research uses survey method with observation technique. The sampling method used the census method, which was to take all the population of grafted rubber nursery farmers in Bentok Darat Village. The population of farmers working on grafting rubber nurseries is 4 people, then all of the grafting rubber nursery farmers in this village are used as respondent farmers in this study. The result of the research is that the average land area used by farmers is 3.5 hectares and the status of land ownership is property rights. The average production is 129,250 trees/farmer or (36,928.57 trees/hectare). The average total cost is Rp 253,504,975.00/farmer, the average fixed cost is Rp 115,896.00/farmer and the average variable cost is Rp 253,389,079.00/farmer. The average income is Rp 646.250.000,00/farmer or Rp. 184.642.857.14/hectare. The profit obtained in one production process is on average Rp 392.745.025.00/farmer or Rp 112,212 .864.28/hectare. The value of the break even point (BEP) seen from the production volume is 38.13 trees and the total sales is Rp 190,649.77 / farmer. At the BEP point there will be a break-even point where the amount of sales is equal to the amount of production.